REPRODUCTIVE BIOLOGY FEMALES Chelonoidis denticulatus, (LINNAEUS, 1766) (TESTUDINIDAE) TRADE IN IQUITOS-PERÚ ABSTRACT - USHIÑAHUA-ALVAREZ, Meri (2022)
In order to contribute to the knowledge of the reproductive condition of the Chelonoidis denticulatus females, commercialized in the Iquitos  city, the evaluation of the reproductive biology of this species was carried out during the period from january to december 2008; thus offering useful technical criteria for the regulation of its consumption, by the regulatory entity. Gonads of benefited specimens were collected in two markets, prior to that each specimen was measured and weighed; In the laboratory, the gonads were macroscopically evaluated, measuring and weighing the oocytes, corpora lutea and oviducal eggs. The results show that, in the markets of Iquitos, females in mature and immature reproductive conditions are sold from various basins; Throughout the year, the gonads showed up to 5 stages of development, not showing a strict seasonal relationship. The smallest sexually mature female had a LCC of 325 mm.